Effect of opaque layer application on the color of resin composites used to fill access openings of screw-retained implant restorations - Çakan, Umut; Kara, Haluk Barış (Quintessence Publishing, 2015)
The purpose of this preliminary in vitro study was to evaluate the effect of an opaque layer and application of resin composite in dual colors on the Delta E values of resin composites used to fill access openings of screw-retained implant restorations. Sixty cylindrical nickel-chromium metal molds with a central channel simulating a posterior screw-retained, implant-supported, porcelain-fused-to-metal crown were cast. Access openings were filled with combinations of opaquer, enamel composite (A2E), dentin composite (A2B and A3B), and resilient composite. Delta E values differed significantly among the groups (P < .01). The combination of opaque layer and dual color resin composites of shades A2E and A3B resulted in significantly lower Delta E values than the other groups (P < .01).
WOS: 000359510400016
PubMed ID: 26218028
Keywords: Opaque Layer; Implant; Composite; Color Resin Composites